Distinct developmental and degenerative functions of SARM1 require NAD+ hydrolase activity. - E J Brace; Kow Essuman; Xianrong Mao; John Palucki; Yo Sasaki; Jeff Milbrandt; Aaron DiAntonio (PLoS Genetics)
SARM1 is the founding member of the TIR-domain family of NAD+ hydrolases and the central executioner of pathological axon degeneration. SARM1-dependent degeneration requires NAD+ hydrolysis. Prior to the discovery that SARM1 is an enzyme, SARM1 was studied as a TIR-domain adaptor protein with non-degenerative signaling roles in innate immunity and invertebrate neurodevelopment, including at the Drosophila neuromuscular junction (NMJ). Here we explore whether the NADase activity of SARM1 also contributes to developmental signaling. We developed transgenic Drosophila lines that express SARM1 variants with normal, deficient, and enhanced NADase activity and tested their function in NMJ development. We find that NMJ overgrowth scales with the amount of NADase activity, suggesting an instructive role for NAD+ hydrolysis in this developmental signaling pathway. While degenerative and developmental SARM1 signaling share a requirement for NAD+ hydrolysis, we demonstrate that these signals use distinct upstream and downstream mechanisms. These results identify SARM1-dependent NAD+ hydrolysis as a heretofore unappreciated component of developmental signaling. SARM1 now joins sirtuins and Parps as enzymes that regulate signal transduction pathways via mechanisms that involve NAD+ cleavage, greatly expanding the potential scope of SARM1 TIR NADase functions.